(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors from 1985 to 1988, gathered several leaves of Pomoideae and Prunoideae affected by mines of Phyllonorycter spp. in different regions of North and Central-South Italy, for the identification and territorial location of species. The main leaf-miners of Rosaceae taken into consideration (apple, quince, peach, apricot, cherry, plum) resulted in Phyllonorycter sp. (? = Lithocolletis pomonella Zeller, sensu Hering, 1966), polyphagous being able to attack apple, quince, cherry, peach, plum, it was widespread and noxious everywhere in North Italy and present, to a certain degree, in the centre (Pisa and Livorno); Ph. blancardellus (F.) was found frequently in apples only in Central - South Italy, with considerably lower ravaging power and density than the previous species; Ph. cerasicolellus (H.-S.) oligophagous, which is more restricted and limited to apricot, peach and plum growing areas, with the exception of apples; however Ph. corylifoliellus (Hb.) was found only on quince. The systematic position of the species of the genus Phyllonorycter living on Malus spp. and other Rosaceae were discussed. Due to the different interpretation of many authors, over the years, various and contrasting opinions were expressed. Biological data on Phyllonorycter sp. and on Ph. cerasicolellus were given, according to research carried out in the province of Ferrara. Morphological and ethological differences between the above mentioned phytophagous, useful for practical identification of the noxious species, were pointed out.